2010
DOI: 10.2460/javma.237.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the prevalence of antimicrobial resistance to macrolide antimicrobials or rifampin in Rhodococcus equi isolates and treatment outcome in foals infected with antimicrobial-resistant isolates of R equi

Abstract: Interpretation of the results emphasized the importance of microbiological culture and antimicrobial susceptibility testing in foals with pneumonia caused by R equi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
136
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(147 citation statements)
references
References 35 publications
5
136
2
4
Order By: Relevance
“…BUCKLEY et al (2007) (GIGUÈRE et al, 2010). Differently, in this study it was not observed significant increase in the MIC values for isolates collected from 1991 to 2013 (P>0.05).…”
contrasting
confidence: 62%
See 3 more Smart Citations
“…BUCKLEY et al (2007) (GIGUÈRE et al, 2010). Differently, in this study it was not observed significant increase in the MIC values for isolates collected from 1991 to 2013 (P>0.05).…”
contrasting
confidence: 62%
“…However, for CLR, the clinical samples showed the major MIC values when compare with R. equi isolates from feces, soil and installations samples (P<0.05). This result is according to selection pressure hypothesis, since rhodococcosis is a chronic disease and repeated treatment can easily target to macrolide resistance (GIGUÈRE et al, 2010). RIBEIRO et al (2006) demonstrated strong efficacy of AZM against Brazilian R. equi isolates (MIC 90 <1.5µg ml -1 ).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…In addition, the use of the 2 classes of drugs in combination reduces the likelihood of development of resistance to either drug 24, 25, 26. This is particularly important given the fact that the prevalence of macrolide resistance among R. equi isolates might be increasing 27. A recent study documented emergence of widespread macrolide resistance at a farm after widespread use of these drugs was instituted for the treatment of foals with subclinical pulmonary lesions 28…”
Section: Discussionmentioning
confidence: 99%